Targeting cytokine signaling in autoimmunity: back to the future and beyond. (December 2016) - Hirahara, Kiyoshi; Schwartz, Daniella; Gadina, Massimo; Kanno, Yuka; O'Shea, John J
Highlights: Targeting JAK–STAT signaling pathway is effective in the treatment of autoimmune diseases. Unlike biologics, Jakinibs block a range of cytokines but their effect can be 'dialed' up or down. Identifying genomic regulatory regions provides clues to targeting signaling pathways. Abstract : Cytokines represent structurally diverse soluble factors with critical roles in normal immune function and the pathogenesis of autoimmunity. The emergence of many successful biological therapies targeting cytokines and cytokine receptors exemplifies the importance of cytokines in driving human autoimmune disease; unsurprisingly, there is no paucity of reviews on this subject. Nonetheless, many patients with autoimmune disease do not respond to biologicals, and cure remains an unmet goal. Thus, targeting the intracellular pathways employed by cytokines provides new therapeutic opportunities. A subset of cytokines utilizes the Janus kinase-signal transducer of activators of transcription (JAK–STAT) pathway as a mode of signal transduction. First generation JAK inhibitors (jakinibs) are used to treat rheumatologic disease, and second-generation jakinibs are being developed. Simultaneously, rapid advances are being made in our understanding of the genomic and epigenomic impact of cytokines. In this review, we will briefly review the role of JAK–STAT-dependent cytokines in immune-mediated disease, the current status of Jakinibs, and future possibilities for therapeutic intervention using genomic insights.